Chaetomium albiziae, a new endophytic species from Albizia lebbeck in Iran - Mehrabi-Koushki, Mehdi; Safi, Atena (Phytotaxa, 2023)
The silk tree (Albizia lebbeck (L.) Benth) is one of the ornamental plants in Ahvaz (southwest of Iran). Two endophytic fungal strains, isolated from the leaves of this plant, were characterized. Molecular phylogenetic analyses based on a combined matrix of the internal transcribed spacer regions 1 and 2 including the intervening 5.8S nuclear ribosomal DNA (ITS), and partial regions of the β-tubulin (tub2) and RNA polymerase II second largest subunit (rpb2) indicated that both strains represent a new Chaetomium species, C. albiziae sp. nov. in the family Chaetomiaceae. Chaetomium albiziae formed a sister lineage with sterile species C. cucumericola. This new species can be characterized by ostiolate perithecia with septate lateral and terminal setae, clavate asci and aseptate ellipsoidal to ovoid ascospores with an apical germ pore. In addition, this is the first report of the endophytic association of the genus Chaetomium with Albizia lebbeck worldwide.